RANCANG BANGUN SISTEM CHATBOT PEMESANANMENU MAKANAN DAN MINUMAN PADA RESTORAN BERBASIS TELEGRAM BOT DENGAN PENDEKATAN NATURAL LANGUAGE PROCESSING - Nur Adl, Waliyin; Dwika Prihambodo, Prakoso; Care Khrisne, Duman; Arsa Suyadnya, I Made; Purnama, Fajar (Jurnal SPEKTRUM, 2024)
In the era of technological advancement, especially in computer and artificial intelligence (AI), there is a significant impact on various fields, including the Food and Beverage business. The use of chatbots with AI technology enables human-computer interaction in natural language, facilitating efficient ordering, information, and customer services. Chatbots are based on Natural Language Processing (NLP) and are trained using Machine Learning techniques such as Artificial Neural Networks (ANN), with TensorFlow as the main tool. This provides ease, accuracy, and efficiency in customer service. From the conducted research, NLP- based reservation chatbots perform well and receive positive feedback from users in most aspects. Keywords: Chatbot, Artificial Intelligence (AI), Artificial Neural Network (ANN), NLP